INFLUENCE OF INTELLECTUAL CAPITAL ON COMPANY GROWTH WITH COMPANY PERFORMANCE AS INTERVENING VARIABLES - Debbianita Debbianita (KINERJA, 2019)
Intellectual capital is one of the knowledge assets owned by a company. This study aims to determine whether intellectual capital has a positive influence on the growth of companies with company performance as an intervening variable. This research takes a sample of companies engaged in hotels, restaurants, and tourism where the sector is one of the critical economic sectors in Indonesia. It is expected that intellectual capital will increase innovation so that it can attract consumers who ultimately improve performance. The data used in this study are financial data for 2009-2015 obtained from the financial statements of each company. The method used is a panel that is processed using e views 6.